Characteristics of the health-promoting properties of Cornus mas - Nawrot, Klaudia; Polak-Szczybyło, Ewelina; Stępień, Agnieszka (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Introduction and aim. The medicinal properties of Cornus mas L. have been used in European and Asian folk medicine for many centuries in the prevention and treatment of many diseases. The high biological activity of the plant results primarily from the presence of valuable ingredients, including anthocyanins, flavonoids and iridoid compounds. The aim of the article is to present the role of bioactive ingredients present in C.mas that determine its health-promoting properties. Material and methods. Review and analysis of the scientific literature. Analysis of the literature. The summarize information about in the field of phytochemical properties and therapeutic effects, among others anticancer, antidiabetic, neuroprotective, cardioprotective and antibacterial. Conclusion. The results of many in vitro and in vivo scientific studies They indicate the possibility of the potential use of Cornelian cherry to obtain valuable nutraceutical and pharmacological substances.
Keywords: bioactive compounds; cornelian cherry; Cornus mas L.; medicinal plant